-2(5t-2)+5t=2t-9

Simple and best practice solution for -2(5t-2)+5t=2t-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5t-2)+5t=2t-9 equation:


Simplifying
-2(5t + -2) + 5t = 2t + -9

Reorder the terms:
-2(-2 + 5t) + 5t = 2t + -9
(-2 * -2 + 5t * -2) + 5t = 2t + -9
(4 + -10t) + 5t = 2t + -9

Combine like terms: -10t + 5t = -5t
4 + -5t = 2t + -9

Reorder the terms:
4 + -5t = -9 + 2t

Solving
4 + -5t = -9 + 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.
4 + -5t + -2t = -9 + 2t + -2t

Combine like terms: -5t + -2t = -7t
4 + -7t = -9 + 2t + -2t

Combine like terms: 2t + -2t = 0
4 + -7t = -9 + 0
4 + -7t = -9

Add '-4' to each side of the equation.
4 + -4 + -7t = -9 + -4

Combine like terms: 4 + -4 = 0
0 + -7t = -9 + -4
-7t = -9 + -4

Combine like terms: -9 + -4 = -13
-7t = -13

Divide each side by '-7'.
t = 1.857142857

Simplifying
t = 1.857142857

See similar equations:

| 118+-5x=-7x+30 | | 5x+1+2x+8=79 | | 10-x*5=5 | | 5(c-4)=3c+6 | | 4w+7-2w+5-2w= | | 0.15-0.2x=0.3(x*3) | | 10p+9-11-p=-2(2p+4)+3(2p+2) | | r-17.1=-48 | | 6x+18y=48 | | (x-8)(x-2)=-9 | | 3k(k+7)=(k-2)(k-2) | | 2x-9x+11=32 | | -4(-4p-5)=2[-2p-3(-p+1)] | | 5x-23+x+29+90=180 | | 2x^2-25x-4=0 | | 15=-12+9x | | 180-108=x | | y=-2x-8x+5 | | x-180=0 | | .77x=28 | | -3x-6y-12=0 | | 18-1x=-7x+30 | | 2x+y=14-3x | | -3n(n^2+2n)= | | 4w+5w+1w= | | x(x+1)(x+2)(x+3)=360 | | 0.333y-0.5=0.1666y | | 4(2x-3)+1=9 | | 3.25=4.3r+16-r | | 2y-6=2x-6 | | ln(x)=.71 | | 6(x-6)+14=6x-21 |

Equations solver categories